Peran Strategic Entrepreneurship dalam Membangun Sustainable Competitive Advantage - Handrimurtjahjo, Agustinus Dedy (Binus Business Review, 2014)
Strategic entrepreneurship has emerged as a new concept in examining convergence in entrepreneurship studies (opportunity-seeking behavior) and strategic management (advantage-seeking behavior). Studies in the area of strategic management have gradually exposed the relationship betweenstrategic management and entrepreneurship: entrepreneurial strategy making; intrapreneurship; entrepreneurial strategic posture within organizations; entrepreneurial orientation; strategic managementintegration as a context for entrepreneurial actions; and entrepreneurship theory with strategic management and the resource-based view (RBV). A conceptual model of SE that has been developed by Ireland et al.suggested that a firm which linearly and sequentially: employs an entrepreneurial mindset to identify opportunities; manages resources strategically to tackle the opportunity; applies creativity and innovation; andgenerates a competitive advantage is strategic and entrepreneurship operation. Managers must maximize the pursuit of new business opportunities while simultaneously maximize the generation and application of temporary competitive advantages to sustainably create organizational value. This paper develops a conceptual framework that demonstrate the role of strategic entrepreneurship in building sustainable competitiveadvantage.